Repercussion of Using Internet Sources: Dilemma for Research Communities - Sharma, Nilakshi; Singh, S.N. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objectives – Consultation of internet sources for educational and research purposes is the new normal. As a result of information communication technology, information creation and access are more convenient. The current study was carried out to investigate the proportion of use of internet sources for research purposes by research scholars of three central universities of North East India, namely Tezpur University, Mizoram University, and Rajiv Gandhi University.Methods – The researchers collected data from 123 respondents through an online questionnaire that was distributed through different social media platforms. The study was conducted among Research Scholars (PhD and M.Phil) of Mizoram University, Rajiv Gandhi University, and Tezpur University.Results – The research results show that research communities are moving toward digital platforms for searching and consulting their required resources. Most of the respondents consult internet sources for writing their research reports, but they do not format the references properly. Some research scholars do not follow any referencing style for citing web documents, and respondents do not have much awareness about the differences between URLs and DOIs. Research communities also face problems due to the inaccessibility of online documents cited by former researchers.Conclusion – Since most of the respondents are not familiar with the use of web archives, the current study suggests that higher education institutions should arrange awareness programs on the use of web archives. Research communities should follow the proper referencing formats to acknowledge others’ works. Publishers should mandate a citation style for authors and verify the accuracy of the references before publishing articles or other works.